Characterization of phoA, a Bacterial Alkaline Phosphatase for Phi Use Efficiency in Rice Plant - Ram, Babu; Fartyal, Dhirendra; Sheri, Vijay; Varakumar, Panditi; Borphukan, Bhabesh; James, Donald; Yadav, Renu; Bhatt, Arun; Agrawal, Pawan K.; Achary, V. Mohan M.; Reddy, Malireddy K. (Frontiers in Plant Science, 2019)
Fertilizers and herbicides are two major components in the agriculture system for achieving crop productivity. Massive use of orthophosphate fertilizers and herbicides poses threats to phosphate reserves and aids the evolution of herbicide tolerant weed biotypes. Phosphite (Phi), a phosphate analog, has been proposed as more beneficial than traditionally used phosphate fertilizers and herbicides in the agriculture. We developed phoA overexpressing transgenic rice that minimizes the phosphate loss and contributes to weed management in the agriculture. The phoA rice lines showed improved root, shoot length and total biomass production under phosphite conditions. Additionally, the complete phenotype and productivity of phoA lines under the phosphite treatment attained was similar to that of plants under phosphate sufficient condition. The Phi metabolizing properties of the phoA overexpressed lines improved under the Phi application and phi treatment enabled controlling of weeds without compromising the yield of transgenic rice plants. Our results indicated that phoA alone or in combination with other Phi metabolizing gene(s) can possibly be used as an effective ameliorating system for improving crop plants for phi-based fertilization and weed management strategy in the agriculture.